USAHA PERTANIAN ORGANIK BERBASIS CSA (COMMUNITY SUPPORTED AGRICULTURE) (STUDI KASUS DI “SENI TANI”, KOTA BANDUNG, INDONESIA) - Diffa Nida Haniyah; Endah Djuwendah; M. Gunardi Judawinata; Agriani Hermita Sadeli (Universitas Galuh, 2022)
Organic vegetables that are mostly consumed by the community in the midst of the rapid development of the organic farming sector, can generally be obtained by purchasing vegetables that have been harvested so that the interaction between consumers and farmers is very limited. However, a concept called CSA (Community Supported Agriculture) that connects farmers with consumers directly and invites consumers to be involved with the production process. Seni Tani is one of the few organic farming businesses that apply the CSA concept in Indonesia. This study aims to explain the type of business and the application of CSA in Seni Tani as an example of the application of CSA in Indonesia which has not been widely carried out. The research design is a qualitative research design with a case study approach. This study uses data collection techniques in the form of observation, in-depth interviews and literature study. The results are indicate that Seni Tani applies regenerative organic agriculture. The plants are organic products and fullfil the principles of health, ecology, justice and protection by imitating natural patterns without adding synthetic chemical inputs. Seni Tani implements social entrepreneurship with a socially responsible enterprise type of business and carries out urban farming activities. CSATani Sauyunan at Seni Tani has fulfilled the CSA concept. CSA Tani Sauyunan fulfills four principles namely partnership, locality, solidarity, and producer-consumer relations. CSA Tani Sauyunan is a small scale CSA that operates informally and can be categorized into the Multi-Farm CSA, Subscription CSA and Mixed-Vegetable CSA types.